KETERIKATAN KERJA (WORK ENGAGEMENT) MAMPU MENINGKATKAN KINERJA KARYAWAN PT. BPRS PATRIOT BEKASI - Sarinah, Lisa; Rachmayanty, Ima (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2021)
In banking industry which is growing quite rapidly along with technological developments, quality employee resources are needed to support the realization of bank performance. This research is expected to make researchers understand the influence of competence, work discipline, work engagement on employee performance in PT BPRS Patriot Bekasi. involving 49 workers. Data analysis utilizes Partial Least Square (PLS), using SmartPLS. The tests used SmartPLS are measurement model (Outer Model) and the structural model (Inner Model). The results of this study indicate that competence has a positive but not significant effect on employee performance. Work engagement has a positive but not significant effect on employee performance. Work discipline has a positive and significant effect on employee performance. Competence has a positive but not significant effect on work discipline. Work engagement has a positive and significant effect on work discipline. Work discipline does not mediate the effect of competence on employee performance. Work discipline mediates the effect of work engagement on employee performance.